TACKLING THE MENACE OF CORRUPTION: NEED FOR A BROAD FRAMEWORK - Aadil Ahmad Shairgojri; Subramanian (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Corruption in India is a pervasive and complex issue that has plagued the country for decades. Despite efforts by successive governments to tackle the problem, corruption continues to be a significant challenge to India's development and progress. This abstract will provide an overview of the problem of corruption in India, including its causes, consequences, and potential solutions. It will examine the role of institutions such as the judiciary, police, and bureaucracy in perpetuating corruption and the impact of corruption on the economy, politics, and society. The abstract will also highlight some of the key initiatives that have been taken to combat corruption in India, including anti-corruption laws, whistleblower protection, and digitization of government services. Finally, the abstract will discuss the challenges that remain in the fight against corruption in India and the need for sustained efforts to address this critical issue.